A look into Phaffia rhodozyma biorefinery: From the recovery and fractionation of carotenoids, lipids and proteins to the sustainable manufacturing of biologically active bioplastics. (October 2022) - Mussagy, Cassamo U.; Remonatto, Daniela; Picheli, Flavio P.; Paula, Ariela V.; Herculano, Rondinelli D.; Santos-Ebinuma, Valéria C.; Farias, Renan L.; S. D. Onishi, Bruno; J. L. Ribeiro, Sidney; F. B. Pereira, Jorge; Pessoa Jr, Adalberto
Graphical abstract: Yeast biorefinery as a promising and sustainable solution for the recovery and fractionation of high-values bioproducts to the manufacturing of bioactive bioplastics Highlights: Phaffia rhodozyma was evaluated as a potential source of bioproducts. Recovery and fractionation of astaxanthin, β-carotene, proteins and lipids. Integration of a sequential operations in a biorefinery approach. Carotenoids to produce sustainable bioactive plastics. Abstract: Carotenoids over-producing yeast has become a focus of interest of the biorefineries, in which the integration of the bioproduction with the following downstream processing units for the recovery and purification of carotenoids and other value-added byproducts is crucial to improve the sustainability and profitability of the overall bioprocess. Aiming the future implementation of Phaffia rhodozyma -based biorefineries, in this work, an integrative process for fractionation of intracellular compounds from P. rhodozyma biomass using non-hazardous bio-based solvents was developed. After one-extraction step, the total amount of astaxanthin, β-carotene, lipids and proteins recovered was 63.11 µg/gDCW, 42.81 µg/gDCW, 53.75 mg/gDCW and 10.93 mg/g, respectively. The implementation of sequential back-extraction processes and integration with saponification and precipitation operations allowed the efficient fractionation and recovery (% w/w) of astaxanthin (∼72.5 %), β-carotene ∼90.17 %), proteins (21.04 %) and lipids (23.72 %). After fractionation, the manufacture of carotenoids-based products was demonstrated, through the mixture of carotenoids-rich extracts with bacterial cellulose to obtain biologically active bioplastics.